Effect of rotation on dusty couple-stress fluid with hydromagnetic field heated below through porous medium. (12th February 2018) - Stanly, W.; Vasanthakumari, R.
Abstract : Purpose: The purpose of this paper is used to study the combined effect of solute gradient and magnetic field on dusty couple-stress fluid in the presence of rotation through a porous medium. Design/methodology/approach: The perturbation technique (experimental method) is applied in this study. Findings: For the case of stationary convection, solute gradient and rotation have stabilizing effect, whereas destabilizing effect is found in dust particles in the system. Couple stress and medium permeability both have dual character to its stabilizing effect in the absence of magnetic field and rotation. Magnetic field succeeded in establishing a stabilizing effect in the absence of rotation. Originality/value: The results are discussed by allowing one variable to vary and keeping other variables constant, as well as by drawing graphs.